Validity and Reliability of Educational Evaluation Tests - Zahfa, Faiz; Fauzi, Ahmad; Yansyah, Erik Aldi; Fadhillah, Farah; Syahdilla, Jivani (Jurnal Riset Ilmu Pendidikan, 2025)
This study aims to test the reliability and validity of a test used in an educational context. Reliability refers to the consistency of test results when applied under different conditions, while validity relates to the extent to which the test measures what it is supposed to measure. In this study, reliability analysis was conducted using the Cronbach's alpha method, while validity was tested through correlation analysis between test scores and relevant criterion measures. The results showed that the test tested had a high level of reliability, with a Cronbach's alpha value reaching 0.85, indicating good internal consistency. In addition, the validity of the test was also found to be adequate, with a significant correlation between test scores and participant performance in relevant tasks. These findings support the use of the test as a reliable and valid measuring instrument in the context of educational evaluation. This study contributes to the development of more objective and measurable assessment instruments in the field of education.